2015
DOI: 10.1021/acs.nanolett.5b03928
|View full text |Cite
|
Sign up to set email alerts
|

Organic Covalent Patterning of Nanostructured Graphene with Selectivity at the Atomic Level

Abstract: Organic covalent functionalization of graphene with long-range periodicity is highly desirable-it is anticipated to provide control over its electronic, optical, or magnetic properties-and remarkably challenging. In this work we describe a method for the covalent modification of graphene with strict spatial periodicity at the nanometer scale. The periodic landscape is provided by a single monolayer of graphene grown on Ru(0001) that presents a moiré pattern due to the mismatch between the carbon and ruthenium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 54 publications
4
36
0
Order By: Relevance
“…Reactivity enhancement at specific topographical features, as patterning induced by moiré superstructures, has been reported for epitaxial graphene on metal1416. We have confirmed that there is not preferential adsorption or nucleation at step edges, buffer layer-induced reconstruction or other morphological defects.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Reactivity enhancement at specific topographical features, as patterning induced by moiré superstructures, has been reported for epitaxial graphene on metal1416. We have confirmed that there is not preferential adsorption or nucleation at step edges, buffer layer-induced reconstruction or other morphological defects.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, only few reactions schemes are available and most of them are promoting direct C–C bond forming reactions with aryl addition89. Other kind of works use ultra high vacuum environments and are usually limited to small molecules, as hydrogen, oxygen or more recently cyanomethyl radicals141516. This kind of works is usually performed for epitaxial graphene grown on metal surfaces and take advantage of the surface patterning obtained by lattice-mismatched graphene on metallic substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, radicals of diazonium salts are able to attach to sp 2 sites but manifests a preference for graphene on hydrophilic substrates [100], due to charge accumulation effects. A similar effect is observed for graphene on metals such as iridium or ruthenium [101,102], where, in addition, a spatially modulated reactivity is created following the nano-metric moiré pattern of corrugation. This open the road to substrate driven functionalization, with the possibility of creating chemical nano-patterns following the symmetry of the moiré superlattice.…”
Section: Multilayers From Epitaxy: a Perspectivesupporting
confidence: 54%
“…1A ) because of their bonding to a different adsorption site. This is possible because the experimental manipulation is carried out at 4.6 K, and hence, the −CH 2 CN radicals do not have enough energy to explore the surface and reach the HCP-top adsorption site where the adsorption energy is maximum ( 25 , 26 ). On the basis of the calculated pDOS, we can rationalize the manipulation process in the following way: Because of the high positive bias voltage (>+1.7 V), the tunneling electrons are injected into the tail of the LUMO of the TCNQ-CH 2 CN.…”
Section: Resultsmentioning
confidence: 99%